Microbial Communities in Model Seawater-Compensated Fuel Ballast Tanks: Biodegradation and Biocorrosion Stimulated by Marine Sediments - Duncan, Kathleen E. (2024)
Some naval vessels add seawater to carbon steel fuel ballast tanks to maintain stability during fuel consumption. Marine sediments often contaminate ballast tank fluids and have been implicated in stimulating fuel biodegradation and enhancing biocorrosion. The impact of the marine sediment was evaluated in model ballast tank reactors containing seawater, fuel (petroleum-F76, Fischer–Tropsch F76, or a 1:1 mixture), and carbon steel coupons. Control reactors did not receive fuel. The marine sediment was added to the reactors after 400 days and incubated for another year. Sediment addition produced higher estimated bacterial numbers and enhanced sulfate reduction. Ferrous sulfides were detected on all coupons, but pitting corrosion was only identified on coupons exposed to FT-F76. Aerobic hydrocarbon-degrading bacteria increased, and the level of dissolved iron decreased, consistent with the stimulation of aerobic hydrocarbon degradation by iron. We propose that sediments provide an inoculum of hydrocarbon-degrading microbes that are stimulated by dissolved iron released during steel corrosion. Hydrocarbon degradation provides intermediates for use by sulfate-reducing bacteria and reduces the level of fuel components inhibitory to anaerobic bacteria. The synergistic effect of dissolved iron produced by corrosion, biodegradable fuels, and iron-stimulated hydrocarbon-degrading microbes is a poorly recognized but potentially significant biocorrosion mechanism.